Analisis Yuridis Peran Media Sosial sebagai Alat Propaganda dan Rekrutmen Kelompok Teror di Indonesia: Tinjauan atas Undang-Undang Nomor 19 Tahun 2016 tentang Informasi dan Transaksi Elektronik - Hidayat Teja (Albayan Journal of Islam and Muslim Societies, 2025)
Social media has become a primary instrument for disseminating radical propaganda and recruiting members of terrorist groups in Indonesia. This study aims to provide a juridical analysis of how terrorist organizations exploit social media, and the effectiveness of Law No. 19 of 2016 on Electronic Information and Transactions (ITE Law) in addressing such threats. Using a normative approach with descriptive-analytical methods, the research finds that platforms such as Telegram, Facebook, and YouTube are strategically utilized to spread extremist ideologies, hate speech, and violent instructions. The study also reveals challenges in law enforcement, including technological limitations, institutional fragmentation, and the ambiguous interpretation of ITE provisions. Therefore, a holistic approach is necessary—incorporating strong legal enforcement, digital literacy enhancement, and international cooperation—to counter digital terrorism propaganda.